Endoscopic resection of symptomatic simultaneous angiolipoma of the colon and duodenum: First case report and literature review - Sanghoon Park; Hoon Jai Chun; Woo Jin Lee; Eun Sun Kim; Bora Keum; Yeon Seok Seo; Yoon-Tae Jeen; Hong Sik Lee; Soon Ho Um; Chang Duck Kim; et al. (Turkish Journal of Gastroenterology, 2019)
-